Fascial turnover flap - an effective method to resolve cartilage exposure after autologous microtia reconstruction - Vlahović Aleksandar; Urošević Aleksandar; Živković Milana (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction. Microtia presents a congenital ear deformity ranging from a minor and barely visible defect to a complete absence of the ear. Currently, there are three options for ear reconstruction: autologous costal cartilage, silicon prothesis, and prosthetic ear. Ear reconstruction with autologous costal cartilage is usually performed in two stages. During the first stage, the cartilaginous framework is fabricated and placed under the skin, in the anatomical position of the ear. In the second stage, the elevation of the frame is performed. During these procedures, complications such as vascular compromise of the skin envelope can occur. Cartilage exposure can lead to its resorption and distortion, leading to an unsatisfactory anatomical result, and this should be resolved as soon as possible. Cartilage exposure at the convex part of the frame is especially problematic. The goal of this paper is to show that fascial turnover flap is a safe method to deal with cartilage exposure as a complication. Outlines of cases. We present two patients with anotia and hemifacial microsomia. Both underwent autologous cartilage microtia repair. In both patients, the cartilage exposure at the convex part of the ear was revealed as a complication. Fascial turnover flap has been used to resolve this complication in both patients. Conclusion. Fascial turnover flap is a safe method to deal with cartilage exposure after microtia reconstruction with autologous cartilage.